European court of human rights case law as a source of European Union law - Boichuk, D.; Hryhoriev, V. (НДІ ПЗІР НАПрН Україна, 2021)
The article is devoted to the study of the legal nature of the decisions of the European Court of Human Rights as a source of law of the European Union. Within the scope of the doctrinal sources and the existing case law of the European Court of Human Rights and the Court of Justice of the European Union, the authors substantiate the logic of including existing the European Court of Human Rights case law in the EU law sources, citing arguments based on the EU law and the case law.
Keywords: EU law; case law of the ECJ; sources of the EU law; ECtHR; ECHR; case law of the ECtHR